Conflict management training for future educators - N. A. Sokolova; N. V. Sivrikova; E. G. Chernikova; T. G. Ptashko; E. M. Harlanova; S. V. Roslyakova (Russian State Vocational Pedagogical University, 2020)
Introduction. The relevance of the declared topic was dictated by the increased conflict between the members of education and the increasing demands placed on the professional activities of the modern teachers to resolve conflicts in the conditions of general education school. In the course of professional training of future teachers in universities, the formation of conflict competence is not paid due attention, so there is a need to determine the role, content and learning technologies for conflict management training of future teachers.The aim of the present publication is to evaluate the effectiveness of conflict management training technology for future teachers.Methodology and research methods. The authors carried out a pedagogical experiment using pre- and post-testing method of the level of formation of the components of conflict readiness of students of a pedagogical university - participants of experimental and control groups. The sample of the experiment was based on 120 of 2nd-4thyear students of the Faculty of History of the South Ural State Humanitarian Pedagogical University of Chelyabinsk. The following methods were used to collect the empirical data: the Thomas test; an achievement test to assess conflict knowledge; practical tasks (cases); methodology "My Conflict Position" (by V. V. Schernyazova). Mathematical processing of the research results was performed through the Pearson's chi-squared test.Results. The differences in the formation of cognitive, technological and personal components in students of the control and experimental group have been established. The dependence of the formation of components of conflict readiness of students for the introduction of a specially developed programme has been determined. After pedagogical impact, the number of students with high cognitive component levels rose from 0 to 39,3%. Most students (97,6%) learned algorithms to solve typical interpersonal conflicts and began to choose more constructive strategies to solve them. In the experimental group after the experiment, the personal component of conflict readiness was higher than in the control group.Scientific novelty. The system is proposed to provide effective conflict management training for future teachers, which consists of three components: immersion in the information field of conflict; intensification of conflict resolution activities; mastering of constructive practices of conflict management.Practical significance. The research results are of particular interest for the development of educational programmes in the system of professional education.